PELATIHAN MENYUSUN DESAIN PEMBELAJARAN INOVATIF BERBANTU FILMORA BAGI GURU DI SMA NEGERI 1 GELUMBANG - Deskoni Deskoni; Firmansyah Firmansyah; Dian Eka Amrina (IKIP PGRI Bojonegoro, 2022)
ABSTRACTThis activity was carried out at SMA Negeri 1 Gelumbang, with a target audience of 21 teachers of various subjects. The activity model used is a mentoring model with technical assistance methods in the preparation of innovative learning designs assisted by the Filmora Application which is carried out by socializing the nature of innovative learning to technical design preparation and making learning videos with the Filmora application which is carried out for two days through zoom meetings. The purpose of this activity is to produce a product in the form of an innovative learning video with the Filmora application. Activity evaluation is carried out by testing and product assessment. The results of the initial knowledge test regarding the nature of innovative learning were an average of 7.04, increasing to an average of 8.96 on the final knowledge test. The increase in test results is 0.43 in the medium category. The product assessment made by the target audience shows that the product made is in the good category with a value of 77.42%. With this service activity, it is hoped that in the future it can contribute to teachers in the form of knowledge and skills in the preparation of innovative learning designs with learning applications.Keywords: Learning design, Innovative Learning, Filmora ABSTRAKPengabdian ini dilaksanakan di SMA Negeri 1 Gelumbang, dengan khalayak sasaran yang berjumlah 21 orang guru berbagai mata pelajaran. Model pengabdian yang digunakan adalah model pendampingan dengan metode pendampingan teknis dalam penyusunan desain pembelajaran inovatif berbantu Aplikasi Filmora yang dilakukan dengan cara sosialisasi mengenai hakikat pembelajaran inovatif sampai pada teknis penyusunan desain dan Pembuatan video pembelajaran dengan Aplikasi filmora yang dilakukan selama dua hari melalui zoom meeting. Tujuan pengabdian adalah menghasilkan produk berupa video pembelajaran inovatif dengan Aplikasi Filmora. Evaluasi kegiatan dilakukan dengan tes dan penilaian produk. Hasil tes pengetahuan awal mengenai hakikat pembelajaran inovatif yaitu rata-rata 7,04, meningkat menjadi rata-rata 8,96 pada tes pengetahuan akhir. Peningkatan hasil tes sebesar 0,43 dengan kategori sedang. Penilaian produk yang dibuat oleh khalayak sasaran menunjukkan bahwa produk yang dibuat termasuk dalam kategori baik dengan nilai sebesar 77,42%. Dengan kegiatan pengabdian ini diharapkan ke depannya dapat memberikan kontribusi bagi para guru berupa pengetahuan dan keterampilan dalam penyusunan desain pembelajaran inovatif dengan Aplikasi pembelajaran.Kata Kunci: Desain pembelajaran, Pembelajaran inovatif, Filmora